2015
DOI: 10.1007/s00464-014-4061-1
|View full text |Cite
|
Sign up to set email alerts
|

Biliary metal stents for proximal esophageal or hypopharyngeal strictures

Abstract: Because of a high clinical success rate and good tolerability, biliary metal stents are a reasonable alternative for difficult strictures in the cervical esophagus, especially in the palliative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…With respect to oesophageal self-expanding metal stents (SEMS), eight recent studies of demonstrated a risk of 0% significant haemorrhage within 7 days of insertion. [150][151][152][153][154][155][156][157] However, studies including delayed haemorrhage showed a risk of 9% in an RCT comparing small-diameter stents with large-diameter stents and an 8% risk in a large retrospective series of 997 patients. 158 159 Causes of haemorrhage included aorta-oesophageal fistula formation, and continued oozing from tumours.…”
Section: Endoscopic Stentingmentioning
confidence: 99%
“…With respect to oesophageal self-expanding metal stents (SEMS), eight recent studies of demonstrated a risk of 0% significant haemorrhage within 7 days of insertion. [150][151][152][153][154][155][156][157] However, studies including delayed haemorrhage showed a risk of 9% in an RCT comparing small-diameter stents with large-diameter stents and an 8% risk in a large retrospective series of 997 patients. 158 159 Causes of haemorrhage included aorta-oesophageal fistula formation, and continued oozing from tumours.…”
Section: Endoscopic Stentingmentioning
confidence: 99%
“…Previous reviews of risks associated with endoscopic stent insertion have been confounded by the variety of stents used and the evolution of stent design with time. With respect to esophageal self-expanding metal stents (SEMS), 8 recent studies of demonstrated a risk of 0 % significant haemorrhage within 7 days of insertion 150 151 152 153 154 155 156 157 . However, studies including delayed haemorrhage showed a risk of 9 % in an RCT comparing small-diameter stents with large-diameter stents and an 8 % risk in a large retrospective series of 997 patients 158 159 .…”
Section: Endoscopic Proceduresmentioning
confidence: 99%
“…Although the use of biliary stents has been described for benign proximal esophageal (hypopharyngeal, cervical) stricture 3 , 4 and rarely benign distal esophageal strictures, 5 their application in malignant disease has not been widely explored ( Fig. 3 A).…”
Section: Distal Esophageal Stricture Secondary To Esophageal Adenocarmentioning
confidence: 99%